Antioxidant of Bulk Cooking Oil from Corn Cob Extract - Roushandy Asri Fardani; Nurul Hadiatun; Yolanda Febriana; Hardani (Jurnal Penelitian Pendidikan IPA, 2025)
Bulk cooking oil is cooking oil produced by the people's industry without packaging, with low quality because it has not used additives to resist oxidation reactions. Along with this, the public's need for bulk cooking oil continues to increase. Bulk cooking oil circulating in the market if stored for a long time can cause a decrease in quality. Thus, antioxidants made from natural ingredients need to be developed. The content of natural materials that can be used as antioxidants in bulk cooking oil is corn cobs. corn cobs contain phenolics, tannins and flavonoids. The study aims to see the ability of corn cob extract as an antioxidant and provide an overview of the quality of bulk cooking oil based on SNI 3741:2013 after the addition of antioxidants. This study used laboratory experimental method, namely the preparation of corn cob extract which was then used as the basic ingredient and formulation of bulk cooking oil with different antioxidant concentrations. The weight of extract added to bulk cooking oil is 2 grams with soaking time of 20, 40, 60 minutes.  The samples were then measured for acid number, iodine, and peroxide. The best results in this study were obtained in the addition of 2 grams of extract and 60 minutes of soaking time showing an improvement in the quality of bulk cooking oil characterized by a decrease in peroxide number and acid number.